Pornography and civil rights: a new day for women's equality - Dworkin, Andrea; MacKinnon, Catharine A. (Organizing Against Pornography, 1988)
"Pornography is central in creating and maintaining the civil inequality of the sexes. Pornography is a systematic practice of exploitation and subordination based on sex which differentially harms women. . . ." With those bold words began the groundbreaking local antipornography law drafted by writer Andrea Dworkin and lawyer Catharine A. MacKinnon. Their completely new legal approach--in which pornography is defined as sex discrimination and therefore a violation of civil rights--would allow anyone injured by pornography to fight back by filing a civil lawsuit against pornographers. First passed in December 1983 in Minneapolis, where it was supported by a grassroots coalition of women, people of color, neighborhood groups, and the city's welfare poor and working poor, this law has transformed the way people of conscience understand the devastating impact of pornography on women's right to equality. This new law also offers hope: an effective legal tool for making sex equality real. In this comprehensive and easy-to-read guidebook, now available on line, the coauthors of the anti-pornography civil-rights ordinance explain: How pornography hurts women and how and why the civil-rights ordinance would make a difference. Why the pornography is so important to women's equality. The truth about the antipornography civil-rights ordinance--what it is, what it does, what it means, how it works. Answers to the lies about it--lies that the media have spread to protect the pornography industry. What you can do to stop the pornographers and further women's equality. "The Ordinance does not take 'rights' away from anyone, . . . it takes the power to hurt women away from pornographers." --from Pornography and Civil Rights
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; cours; discipline; droit; droits des femmes*; féminisme anti-porn; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; science politique et droit; sex1911; sexualité; sofia; thématiques; violences; états-unis

Women, violence and social control - Hanmer, Jalna; Maynard, Mary (Humanities, 1987)
Keywords: amériques; continuum de violences; cours; discipline; europe; royaume-uni; régions géographiques; sciences humaines; sociologie; thématiques; trs3500; violences; violences conjugales; violences contre les femmes*; états-unis

Des cailloux blancs pour les forêts obscures - Marchessault, Jovette (Collection Roman québécois, 1987)
Qualifié à sa parution en 1987 de « roman du troisième œil » par Gloria F. Orenstein, ce livre raconte un moment dans la vie de Jeanne – depuis sa retraite des Appalaches, au sein d’une petite communauté d’esprits nouveaux –, alors que se meurt sa compagne, Noria. Aviatrice, cette dernière sauve des laboratoires les bêtes torturées à des fins de recherches expérimentales. Sur le seuil de sa vie revient son père, le Lion de Bangor, avec qui elle s’était réconciliée. Ce médecin, qui étudie les cellules souches du cancer, lève enfin pour Jeanne l’écrivaine les derniers voiles sur la vie de Noria : sa naissance, son enfance au sein du Ku Klux Klan, ce fils qu’elle a perdu, et cet amour infini que le Lion lui porte, un amour « comme ces ponts miraculeux sur lesquels nous avançons les uns vers les autres. » « Ce dernier volet de la trilogie Comme une enfant de la terre met en scène Noria, une aviatrice qui, telle une chamane, vole à travers le ciel nocturne de l’Amérique du Nord pour livrer au monde un message de salut et un espoir de guérison, et Jeanne, l’écrivaine qui pratique son propre art magique de la guérison : l’art de la littérature. » — GLORIA F. ORENSTEIN
Keywords: 1900-1999; amériques; approches et analyses; care; histoire et politique; hétérosexisme; littérature québécoise; périodes historiques; racisme; roman; régions géographiques; santé; sexisme; systèmes d'oppressions; thématiques; violences

Jeunes femmes et « contre-culture » au Québec - Lamont, Ève (Les Cahiers du Grif, 1986)
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; patriarcat; périodes historiques; québec; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques; violences

Female sexual slavery - Barry, Kathleen (New York University Press, 1984)
Keywords: amériques; corps; cours; cycles supérieurs; discipline; fem1000; fem7000; fem9000; lit3220; premier cycle; prostitution; régions géographiques; sciences humaines; sociologie; thématiques; violences; états-unis

The Traditional Roles of Native Women in Canada and the Impact of Colonization - Brodribb, Somer (The Canadian Journal of Native Studies, 1984)
Recent trends in feminist research indicate a growing interest in the impact of Native women on westward expansion and imperialism. The author suggests that while early European contacts affected the status of women negatively, the views of Native women were seldom recorded during these early contact periods. Recent studies have examined the status and changing roles of Native women from the viewpoints of contemporary Native women. The diversity of their opinions continues to be a part of the contemporary debate on the resilience and resourcefulness of Native women in the past.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; 1970-1979; 1980-1989; amériques; approches et analyses; canada; cours; discipline; famille; féminisme autochtone; histoire et politique; intersectionnalité; mariage; pol4105; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sexisme; sociologie; sofia; système colonial; systèmes d'oppressions; thématiques; violences

Pleasure and danger: Exploring female sexuality - Vance, Carole S. (Routledge & Kegan Paul, 1984)
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; cours; plaisir féminin; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sex1183; sexualité; sexualité des femmes*; thématiques; violences; états-unis

Thinking Sex: Notes for a Radical Theory of the Politics of Sexuality - Vance, Carole S. (Pleasure and danger: exploring female sexuality, 1984)
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; cours; plaisir féminin; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sex1183; sexualité; sexualité des femmes*; thématiques; violences; états-unis

Resistance to oppression: Black women's response to slavery in the united states - Ellison, Mary (Slavery & Abolition, 1983)
Keywords: afro-féminisme; amériques; approches et analyses; cours; esclavagisme; fem3100; femmes* afro-américaines; féminisme afroaméricain; histoire et politique; militance; premier cycle; racisme; régions géographiques; sexisme; systèmes d'oppressions; thématiques; violences; états-unis

L'Envers de la nuit: les femmes contre la pornographie - Lederer, Laura; Audy, Monique; Dufresne, Martin (Collection Les Entêtées, 1983)
Keywords: 1900-1999; amériques; approches et analyses; corps; cours; discipline; droit; féminisme pop; premier cycle; psychologie; périodes historiques; régions géographiques; science politique et droit; sciences humaines; sex1911; sexisme; sexualité; systèmes d'oppressions; thématiques; violences; états-unis

La Mère des herbes - Marchessault, Jovette (Réelles, 1980)
Second volet d'une trilogie romanesque intitulée Comme une enfant de la terre. Le premier volet (Le crachat solaire) a obtenu le Prix France-Québec 1976. Imprécations et transgressions. Un roman "autobiographique et épique", violent, incantatoire, poétique, révolté. L'héroïne est une petite Québécoise élevée dans une culture de violence (mâle et chrétienne) et d'intimidation, qui raconte ses expériences et ses intuitions, les instants de bonheur passés avec sa grand-mère autochtone, pianiste et guérisseuse, etc.
Keywords: amériques; approches et analyses; autobiographie; enfance; littérature québécoise; patriarcat; québec; roman; régions géographiques; systèmes d'oppressions; thématiques; violences; écriture des femmes*

L'orientalisme : l'Orient créé par l'Occident - Said, Edward W. (Seuil, 1980)
D'Eschyle à Kissinger, de Marx à Barrès, l'Occident a tenu un discours sur l'Orient. Mais, puisque «l'Orient» n'existe pas, d'où vient ce discours et comment expliquer son étonnante stabilité à travers les âges et les idéologies? «L'Orient» est une création de l'Occident, son double, son contraire, l'incarnation de ses craintes et de son sentiment de supériorité tout à la fois, la chair d'un corps dont il ne voudrait être que l'esprit. À étudier l'orientalisme, présent en politique et en littérature, dans les récits de voyage et dans la science, on apprend donc peu de choses sur l'Orient, et beaucoup sur l'Occident. Le portrait que nous prétendons faire de l'Autre est, en réalité, tantôt une caricature, tantôt un complément de notre propre image. L'idéologie orientaliste s'est échappée depuis longtemps déjà du cabinet des savants pour précéder Napoléon dans sa conquête de l'Égypte ou suivre la guerre du Liban. C'est de ce discours qu'on trouvera ici la magistrale archéologie, augmentée de la préface que l'auteur rédigea en 2003 pour le vingt-cinquième anniversaire de la publication originale de l'ouvrage.
Keywords: amériques; approches et analyses; arts; com5170; cours; discipline; discours dominant; europe; fem1000; fem3400; féminisme décolonial; har4600; har4610; occident; orient; premier cycle; régions géographiques; systèmes d'oppressions; thématiques; violences; études littéraires